Analiza porównawcza rozwoju wybranych banków komercyjnych w latach 2001–2009 - Konopka, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Throughout the last decade, Bank Pekao S.A., ING Bank Śląski, Bank Zachodni WBK, Bank Millenium and BPH S.A were among those with the highest consolidation activity. Above-listed banks ranked in the top ten in terms of their assets and market capitalization in 2009. The work presents comparative study of development for those commercial banks. The analysis was conducted employing the sustainable development synthetic mesure, relative development rate index and Ward’s metod. Comparative study of development revealed how volatile the development process was with the Bank BPH S.A. showing the most fluctiuations in the process. In 2003 the bank ranked as the best while in 2008–2009 it was classified as the weakest. The study using the relative development index asserted the high ranking of Bank Pekao S.A. when compared to others. The analysis with Ward’s method proved that throughout 2001–2006 the distance among banks with respect to the selected characteristics was becoming less pronounced